I ringen med Hitler - jødisk idræt i 30'ernes Danmark - Olsen, Nina Skyhøj (Rambam. Tidsskrift for jødisk kultur og forskning, 2012)
Wrestling with Hitler In 1936, the Olympic Games were held in Berlin. As the only association in the Danish Sports Federation (DIF), The Danish-Jewish sports association Hakoah chose to boycott the Games. This decision was not easy to make. One of Denmark's best wrestlers at the time, Abraham Kurland, was on Hakoah’s team, and he was considered a realistic candidate for an Olympic medal. Initially, Hakoah took a stand against a boycott because, in their view, sports and politics ought to be kept separate. Eventually, though, they had to acknowledge that the interest of the Jewish community and the boycott's symbolic value was more important than an Olympic medal. The decision to boycott was, however, not taken overnight. It was the result of a yearlong process and debate in the Jewish community in Denmark. The heated debate in the Danish-Jewish press started in 1934 when the boxing brothers Demsitz were invited to participate in a boxing event in Germany organized by a German/Jewish sports club. The Jewish community in Denmark was generally against having any kind of relations with Nazi Germany, but at the same time, many were aware that Jewishathletes were struggling and in need of support. One side argued that Danish-Jewish athletes should stay out of Germany in protest as long as the situation did not improve for the Jews in Germany – while Hakoah argued that the Jewish community should support the sporting activity, as this could serve as an encouragement to the German Jews in their time of need. The two parties never came to an agreement on the matter. The brothers Demsitz didn’t accept the invitation to go to Germany, while Hakoah continued its cooperation with the Jewish sports clubs in Germany until the boycott of the Olympics in 1936.